2012
DOI: 10.1200/jco.2011.36.8399
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Race, Insurance, Socioeconomic Status, and Hospital Type on Receipt of Guideline-Concordant Adjuvant Systemic Therapy for Locoregional Breast Cancers

Abstract: Sociodemographic and hospital factors are associated with guideline-concordant use of systemic therapy for breast cancer. The identification of modifiable factors that lead to nonguideline treatment may reduce disparities in breast cancer survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(120 citation statements)
references
References 30 publications
5
110
5
Order By: Relevance
“…These results contradict those of studies examining socio economic status and access to health care in other countries. 29,30 Specific ally in cancer care, differences in socio economic status have been found for several different types of cancer [31][32][33][34] and may influence cancer-related outcomes. Canada's public health care system mandates equal access for all patients, regardless of socio economic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results contradict those of studies examining socio economic status and access to health care in other countries. 29,30 Specific ally in cancer care, differences in socio economic status have been found for several different types of cancer [31][32][33][34] and may influence cancer-related outcomes. Canada's public health care system mandates equal access for all patients, regardless of socio economic status.…”
Section: Discussionmentioning
confidence: 99%
“…We included adult patients (aged 18-80 yr) with resectable colon cancer who were surgically treated in Ontario between Jan. 1, 2002, and Dec. 31,2008. Patients were identified using the Ontario Cancer Registry (OCR), in which they were registered at the time of surgical specimen or cancer biopsy.…”
Section: Methodsmentioning
confidence: 99%
“…14 More than two thirds of premenopausal women with breast cancer, 15,16 but only 15% to 30% of older women age Ն 65 years, receive adjuvant chemotherapy. 13,15,[17][18][19] A few studies have explored reasons for nonreceipt of adjuvant chemotherapy and identified factors related to the patient, the physician, and patient-physician communication.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R T V Omentioning
confidence: 99%
“…Understanding the reasons for differences between 'real-world' treatment decisions and guideline recommendations will enable further guideline clarification. Furthermore, lack of adherence to the guideline-recommended treatments may negatively affect quality of care in patients with BC 2,[7][8][9] . This chart review is the first that evaluates actual physician-reported treatments from adjuvant therapy to completion of three lines of treatment in the advanced BC setting for the purpose of providing evidence of HT and chemotherapy treatment patterns in Europe and assessing the results against guideline recommendations in order to highlight issues requiring further clarification.…”
Section: Introductionmentioning
confidence: 99%